Exploring Nurses Self-Efficacy Regarding Nursing Competencies among Associate Nurses in Bali, Indonesia - I Ketut Dian Lanang Triana; Vip Paramarta; Rukhiyat Syahidin; Farida Yuliaty; Kosasih Kosasih; Ni Putu Emy Darma Yanti (Indonesian Journal of Global Health Research, 2025)
Nurses’ self-efficacy refers to their perception of their own capability to carry out specific tasks, which in turn can influence various aspects of practice aimed at delivering improved nursing care. This study aimed to identify and explore nurses’ self-efficacy in relation to nursing competencies and its predictors among nurses in Bali, Indonesia. This study employed a descriptive-analytical design involving 149 associate nurses choosen by purposive sampling. Data were collected using questionaires and Pearson’s correlation test is employed to examine the relationships between variables. This study found that nurses’ self-efficacy was influenced by their length of work experience. In addition, burnout syndrome, self-esteem, and grit were identified as significant predictors of nurses’ self-efficacy. This study implied that the nurses’ self-efficacy regarding nursing competencies could be improved as long as the nurses has their optimum personal characteristics as well as self-functionality. Thus, will affects their professional nursing competencies in order to improve better nursing outcomes.